2022
DOI: 10.26434/chemrxiv-2022-lpjl9-v2
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Structural, Dynamical, and Entropic Differences Between SARS-CoV and SARS-CoV-2 s2m Elements Using Molecular Dynamics Simulations

Abstract: The functional role of the highly conserved stem-loop II motif (s2m) in SARS-CoV and SARS-CoV-2 in the viral lifecycle remains enigmatic and an intense area of research. Structure and dynamics of the s2m are key to establishing a structure-function connection, yet a full set of atomistic resolution coordinates is not available for SARS-CoV-2 s2m. Our work constructs three-dimensional coordinates consistent with NMR solution phase data for SARS-CoV-2 s2m and provides a comparative analysis with its counterpart … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 50 publications
0
2
0
Order By: Relevance
“…We and others have analyzed the SARS-CoV-2 3'-UTR for potential binding sites for host miRs (6,7,11,33,54,55) and identified that miR-760-3p has a predicted binding site located at nt 29,833 -29,856 in the reference SARS-CoV-2 genome (NCBI: NC_045512.2) (Fig. 1, nt 272-313 in the 3'-UTR, turquoise dashed line) and that miR-34a-5p and miR-34b-5p both have the same predicted binding site, downstream of the s2m, extending into the lower stem of the s2m (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We and others have analyzed the SARS-CoV-2 3'-UTR for potential binding sites for host miRs (6,7,11,33,54,55) and identified that miR-760-3p has a predicted binding site located at nt 29,833 -29,856 in the reference SARS-CoV-2 genome (NCBI: NC_045512.2) (Fig. 1, nt 272-313 in the 3'-UTR, turquoise dashed line) and that miR-34a-5p and miR-34b-5p both have the same predicted binding site, downstream of the s2m, extending into the lower stem of the s2m (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, this motif was also shown to bind host cellular microRNA (miR)-1307-3p in vitro. (6,7) With this in mind, we investigated whether the SARS-CoV-2 viral genome 3'-UTR could undergo additional interactions with host miRs, based on secondary structural elements.…”
Section: Introductionmentioning
confidence: 99%